Development of a Minimum Competency Assessment (AKM ) Based on a Computer Based Test ( CBT ) to Measure Scientific Literacy and Numeracy Abilities - Wulandari, Anggun; Sudarmin, Sudarmin; Subali, Bambang; Saptono, Sigit (Universitas Negeri Semarang, 2024)
The Minimum Competency Assessment (AKM) is a measure of literacy and numeracy achievements, which is used to map the quality of education in Indonesia against international standards. To achieve the demands of the 21st century, one important aspect is assessment. Computer Based Testing (CBT) can be used as a solution for conducting digital assessments. This research aims to determine the quality and feasibility of the AKM instrument for scientific literacy and numeracy. This research method is R&D with the ADDIE type. This research sample used a purposive sampling technique with a sample of 100 students. Expert Validation is carried out by 5 validators. The results of the research show that the development of CBT-based A K M to measure scientific literacy and numeracy skills has very good quality with the average result obtained for scientific literacy being 4.66 and numeration obtaining an average validation score of 4.77. with the